Living on the streets: An integrative review about the care for homeless people - Fabiana Ferreira Koopmans; Donizete Vago Daher; Sonia Acioli; Vera Maria Sabóia; Crystiane Ribas Batista Ribeiro; Carine Silvestrine Sena Lima da Silva
ABSTRACT Objective: To identify essential elements in care practices for the Homeless Persons in the context of Primary Health Care and verify evidence and strength of recommendation for health decision-making. Method: Integrative literature review, using Health Descriptors, keywords and "MeSH terms" in the databases: LILACS, PubMed Centre and Web of Science. Results: Twenty-two scientific papers were selected and grouped into three categories: Understanding of the Other, Support Network and Emancipatory Care. The study identified important elements for the development of care, such as understanding Homeless Persons, valuing network care and Emancipatory Care. Conclusion: There was a need for further studies and research on the subject, which would make it possible to construct more equitable and inclusive health policies and actions for this population that needs very unique elements in care practices.